(untitled) (Economic and Political Thought, 2016)
For Poland, the OECD and EU accession meant that it would join the assistance programmes designed for international development cooperation. This activeness has raised controversies among the Polish society and politicians since the very beginning because Poland is to change from a beneficiary state into a donor state. The Ministry of Foreign Affairs and the Development Cooperation Department, which is in its structure, are mainly responsible for assistance for Poland. Since 2015, we are obliged to submit 0.33% of the GDP to the EU budget but we do not fulfil the requirement. The resources we managed to gather are transferred to the so-called priority countries, i.e. Belarus, Georgia, Moldova and Ukraine as well as Ethiopia, Kenya, Myanmar, Palestine, Senegal and Tanzania.